2012
DOI: 10.1007/s11098-012-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge entails dispositional belief

Abstract: Knowledge is widely thought to entail belief. But Radford has claimed to offer a counterexample: the case of the unconfident examinee. And Myers-Schulz and Schwitzgebel have claimed empirical vindication of Radford. We argue, in defense of orthodoxy, that the unconfident examinee does indeed have belief, in the epistemically relevant sense of dispositional belief. We buttress this with empirical results showing that when the dispositional conception of belief is specifically elicited, people's intuitions then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 39 publications
3
33
0
3
Order By: Relevance
“…Indeed, asRose and Schaffer (2013), andBuckwalter et al (2013) argue, they are capable of constituting knowledge.18 Additionally, there will still be a proliferation of very similar coarse grained epistemic candidates. Coarse grained propositions can differ in fine grained ways.…”
mentioning
confidence: 99%
“…Indeed, asRose and Schaffer (2013), andBuckwalter et al (2013) argue, they are capable of constituting knowledge.18 Additionally, there will still be a proliferation of very similar coarse grained epistemic candidates. Coarse grained propositions can differ in fine grained ways.…”
mentioning
confidence: 99%
“…One of the findings of this study was the confirmation of consistency between teachers' beliefs and their classroom practices as a key factor in the promotion of quality relationships with children. Whilst dispositional beliefs (Rose and Schaffer 2013) refer to a belief that is not currently being considered but located deep within a person's memory, whilst occurrent beliefs refer to beliefs that are currently being considered. The participating Soka educators demonstrated that their dispositional and occurrent beliefs (Rose and Schaffer 2013) were consistently in line.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst dispositional beliefs (Rose and Schaffer 2013) refer to a belief that is not currently being considered but located deep within a person's memory, whilst occurrent beliefs refer to beliefs that are currently being considered. The participating Soka educators demonstrated that their dispositional and occurrent beliefs (Rose and Schaffer 2013) were consistently in line. These ingrained beliefs are due to their underlying Buddhist philosophy, which leads them to use these concepts in their daily practice and everyday lives, and is reflected in their routine classroom activities.…”
Section: Methodsmentioning
confidence: 99%
“…9 For Anti-Intellectualist explanations of this latter sort of case, see Noë (2005), Setiya (2012), and Michaelson,ms. 10 The thesis that knowledge entails belief has been endorsed in Cohen (1966), Armstrong (1969Armstrong ( , 1973, Sorensen (1982), Dartnall (1986), Rose and Schaffer (2012) and Ichikawa and Steup (2014); among others. 11 Wallis' cases are themselves drawn from Luce and Segal (1966) and Schacter (1989), respectively.…”
Section: Extant No-belief Casesmentioning
confidence: 99%
“…For counter-arguments to the luminosity of belief thesis, seeRose and Schaffer (2012) andBuckwalter et al (2013).33 See, for instance,Nagel (2013).34 To be clear, these implicit beliefs in which we are interested are standing beliefs. That is, they are long-term, stable states of the agent rather than just fleeting implicit or unconscious states-though the existence of the latter sort of state is certainly a distinct possibility.…”
mentioning
confidence: 99%